The Application of Fuzzy Logic for the Quality of Salted Egg - Denita Dwi Maharani; Fiqri Nurfadillah; Muhammad Danang Mukti Darmawan; Nanda Octavia; Ester Angelina; Danish Ardian Pangestu; Nazwa Zulfa Fadilah; Amelia Indah Pariansyah; Salsabila Az-Zahrah; Viony Amelia; Intan Nurmaharani; Nailah Ghaida Putri Prabowo; Cika Ridha Rismawati; Faida Nur Zakiyah; Annisa Intan Handayani; Mrr. Lukie Trianawati; Awwalu Rohadatil 'Aisy (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
Salted eggs are a typical Indonesian food whose processing process is through dry or wet salting. The process of processing salted eggs aims to increase added value and extend the shelf life of duck eggs. This study was conducted to analyze the quality of salted eggs in the practicum of IPB Food Quality Assurance students, based on organoleptic tests with the most preferred flavor, texture, and over-ripening parameters. Assessment of the quality of salted eggs is done by organoleptic test by assessing the level of liking to 27 panelists. Because the 3 variables used are vague, so the variables and parameter determination are uncertain. Due to the uncertainty of the variables and parameters used, fuzzy logic is used with the Mamdani method to help make decisions. The results showed in the sample that salted eggs made with rubbed ash and salt ratio (2: 1) had good quality with a quantitative value of 7.5. Salted eggs with good quality, means that salted egg samples are acceptable to panelists.